PENGARUH KOMITMEN ORGANISASI, PENGENDALIAN INTERN AKUNTANSI, PERAN INTERNAL AUDIT, PENDIDIKAN, DAN KUALITAS PELATIHAN TERHADAP KETERANDALAN LAPORAN KEUANGAN PADA SKPD PEMERINTAH KABUPATEN HALMAHERA UTARA - Dodopo, Yoki; Sondakh, Jullie; Tinangon, Jantje (Universitas Sam Ratulangi, 2017)
Abstract. This research aims to test the influence of such independent variables as the organizational commitment, Accounting Internal Control, The Role Of Internal Audit, Education, and the quality of training to such dependent variables as the reliability of the financial report of local government. This research uses a quantitative approach, using primary data through questionnaires. The respondents in this study were Â the employees who processes the financial administration and those who make financial report at the Local Working Unit (SKPD) in North Halmahera Regency Government. The population used for this research is a group of financial staff which is about 298 people in each of the SKPD, and the samples taken areÂ 75 respondents. The data were analyzed using multiple linear regression analysis and the data were tested by using SPSS program version 22. The results of a multiple linear regression analysis shows that partially, the organizational commitment, accounting internal control, the role of internal audit, education, and the quality of training give positive impacts and significant effects to the reliability of the financial report of local government. The result of the test also shows that simultaneously, the good organizational commitment, accounting internal control, the role of internal audit, education, and quality of training give positive impacts and significant effects to the reliability of financial report of local government. The value of the coefficient of determination indicates that the organizational commitment, accounting internal control, the role of internal audit, education, and quality of training is 49.70%, and the remaining 50.30% is affected by other factors which are not included in this model of research. Keywords : Organizational Commitment, Internal Control Of Accounting, The Role Of Internal Audit, Education, Quality Of Training, The Reliability Of Financial Report.